A policy proposal to deal with excessive cultural tourism - Bruno S. Frey; Andre Briviba (Center for Research in Economics, Management and the Arts (CREMA), 2021)
This paper presents a proposal to deal with cultural overtourism causing substantial negative e!ects. They burden the local population, tourists, and the natural environment by overcrowding, vandalism, and pollution. While at present tourism is suppressed by governments due to the COVID-19 pandemic, it will likely become a major issue again in the future. Our proposal allows us to think about the way cultural tourism should be organized in the future and how to mitigate the negative externalities a!ecting cultural heritage as well as the local population and the natural environment. As an innovation to overcome these problems, the heavily visited historical sites are to be replicated in a suitable nearby location. Advanced digital technology such as augmented and virtual reality, holograms, and digital twins are to be used to make the cultural sites attractive to all sorts of tourists.
Keywords: D62; P48; Z10; Z18; Z38; Z30; 330; Overtourism; innovation; Revived Original; copy; digital technology